2014
DOI: 10.1126/science.1235681
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Principles for the Therapeutic Exploitation of Glycosylation

Abstract: Glycosylation plays a key role in a wide range of biological processes. Specific modification to a glycan's structure can directly modulate its biological function. Glycans are not only essential to glycoprotein folding, cellular homeostasis, and immune regulation but are involved in multiple disease conditions. An increased molecular and structural understanding of the mechanistic role that glycans play in these pathological processes has driven the development of therapeutics and illuminated novel targets fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
309
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(313 citation statements)
references
References 98 publications
1
309
0
3
Order By: Relevance
“…2A), as expected for the removal of all the three highmannose N-glycans. Unexpectedly, MALDI-TOF MS analysis of the N-glycans released by PNGase F showed two major molecular ions: one with an m/z of 1257.3 that matches N-glycan Man 5 (Fig. 2B).…”
Section: Characterization Of Epo Produced From the Hek293smentioning
confidence: 99%
See 2 more Smart Citations
“…2A), as expected for the removal of all the three highmannose N-glycans. Unexpectedly, MALDI-TOF MS analysis of the N-glycans released by PNGase F showed two major molecular ions: one with an m/z of 1257.3 that matches N-glycan Man 5 (Fig. 2B).…”
Section: Characterization Of Epo Produced From the Hek293smentioning
confidence: 99%
“…1). However, the discovery of core-fucosylated Man 5 GlcNAc 2 glycan from natural proteins of a GnT I knockout CHO cell lines by Lin et al (13) provided the first evidence suggesting the presence of a GnT I-independent pathway for core fucosylation of Man 5 GlcNAc 2 and paucimannose glycans in mammalian systems. Later on, Crispin et al (14) reported the detection of minor fractions (ϳ5%) of core-fucosylated, highmannose glycoforms in recombinant glycoproteins produced in GnT I knockout CHO and human HEK293S cell lines, confirming the presence of a GnT I-independent fucosylation pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the complex type N-glycan, the specificity of Endo-S2 was further tested with high-mannose type (HM) Man 9 GlcNAc oxazoline (7) and sialo hybrid type (Hyb) Neu5AcGalGlcNAcMan 5 GlcNAc oxazoline (5) as donor substrate in the transglycosylation reactions. The reactions led to the formation of the corresponding homogeneous glycoforms, (8) and (6), respectively (Fig.…”
Section: Comparative Study On the Hydrolysis And Transglycosylationmentioning
confidence: 99%
“…Recent advances in material chemistry, especially with introduction of various nanomaterials, together with launching of novel transducing protocols and biorecognition elements are behind a huge development in ultrasensitive and multiplexed analysis of a wide range of disease biomarkers [18][19][20][21][22][23]. It is well-known that presence of labels can negatively affect binding [24,25] and thus label-free methods of analysis are preferential option for diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%